2000
DOI: 10.1161/01.atv.20.9.2148
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Electrophoretic and Size Subclasses of Apolipoprotein A-I–Containing Particles in Human Peripheral Lymph

Abstract: Abstract-When cultured cells are exposed to plasma, the initial acceptors of unesterified cholesterol are small lipid-poor apolipoprotein A-I (apoA-I)-containing high density lipoproteins (HDLs) with pre-␤ electrophoretic mobility. These are converted by lecithin:cholesterol acyltransferase into larger spheroidal cholesteryl ester-rich HDLs with ␣ mobility. To study the determinants of the concentration of small pre-␤ HDLs in tissue fluids, we collected prenodal peripheral lymph from 34 fasted normal men. By c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…Although treatment of the membrane with glutaraldehyde (34 ) should prevent losses after electrotransfer, some losses may already have occurred. We have shown in two independent studies that the pre-␤ apo A-I concentration measured by our assay over a wide range of values in plasma and lymph is in good agreement with that obtained by high-performance size-exclusion chromatography (28,29 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although treatment of the membrane with glutaraldehyde (34 ) should prevent losses after electrotransfer, some losses may already have occurred. We have shown in two independent studies that the pre-␤ apo A-I concentration measured by our assay over a wide range of values in plasma and lymph is in good agreement with that obtained by high-performance size-exclusion chromatography (28,29 ).…”
Section: Discussionsupporting
confidence: 79%
“…The inter-and intraassay CV for pre-␤ apo A-I concentration were Ͻ5%. This assay measures total apo A-I in all pre-␤-HDL particles of different sizes, is unaffected by storage of plasma at Ϫ70°C for several months, and has been shown in two independent studies to give results that are in excellent agreement with those obtained by high-performance size-exclusion chromatography (28,29 ).…”
Section: Laboratory Proceduresmentioning
confidence: 78%
See 1 more Smart Citation
“…28 -30 It is also important to note that relative to the concentration of lipid-rich ␣-HDL, the concentration of these lipid-poor particles is increased in extravasal compartments including the lymph, where RCT is initiated in vivo. 27,31,32 ␣-HDL can be further differentiated by ultracentrifugation according to density (HDL 2 and HDL 3 ), by nondenaturing polyacrylamide gradient gel electrophoresis according to size, or by immunoaffinity chromatography according to apolipoprotein composition (eg, LpA-I/A-II and LpA-I). 25 …”
Section: Hdl Subclassesmentioning
confidence: 99%
“…These authors reported that the concentration of small pre-␤ HDL in tissue fluids is determined only in part by the transfer of pre-␤ HDL across capillary endothelium from plasma. Therefore, local production of pre-␤ HDL by remodeling of spherical HDL in tissue fluids may contribute as well (47). The demonstration that PLTP is expressed in macrophages suggests that it could influence the remodeling of large spherical HDL to generate FC-poor pre-␤ HDL or FC-rich apoA-I in the intima of atherosclerotic lesions.…”
Section: Downloaded Frommentioning
confidence: 99%